2022
DOI: 10.3390/vaccines10081212
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydrophobic Amino Acids) and Liposomes for Delivery of Vaccine against Group A Streptococcus

Abstract: Adjuvants and delivery systems are essential components of vaccines to increase immunogenicity against target antigens, particularly for peptide epitopes (poor immunogens). Emulsions, nanoparticles, and liposomes are commonly used as a delivery system for peptide-based vaccines. A Poly(hydrophobic amino acids) delivery system was previously conjugated to Group A Streptococcus (GAS)-derived peptide epitopes, allowing the conjugates to self-assemble into nanoparticles with self adjuvanting ability. Their hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Hence, this novel platform has several new aspects compared to the existing protein-based anti-METH vaccine platforms. One can further optimize antibody responses by using self-adjuvanting tricomponent vaccines that include antigen-glycoprotein-universal T helper epitope PADRE and Pam 3 CysSer adjuvant [51][52][53] or the use of nanoparticles [54][55][56]. Previous research on the efficacy and stability of relevant candidate MS vaccine using oxidized mannan conjugated with antigenic epitope peptide MOG35-55 is in line with and supports the findings of this study [57,58].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, this novel platform has several new aspects compared to the existing protein-based anti-METH vaccine platforms. One can further optimize antibody responses by using self-adjuvanting tricomponent vaccines that include antigen-glycoprotein-universal T helper epitope PADRE and Pam 3 CysSer adjuvant [51][52][53] or the use of nanoparticles [54][55][56]. Previous research on the efficacy and stability of relevant candidate MS vaccine using oxidized mannan conjugated with antigenic epitope peptide MOG35-55 is in line with and supports the findings of this study [57,58].…”
Section: Discussionsupporting
confidence: 86%
“…This implies that CD40 may serve as a reliable marker for indicating the production levels of TNF-α and IL-10. As previously reported, all poly(hydrophobic amino acids)-containing vaccine formulations (J8-K(V 10 )-PADRE, J8-K(F 10 )-PADRE, J8-K(L 10 )-PADRE, J8-K(L 15 )-PADRE, and L 15 -PADRE-J8) self-assemble into nanoparticles ( 13 , 21 , 27 , 28 ), which facilitate their recognition by APCs, including DCs, thereby enhancing the internalization of vaccine components and further accelerating the processing of antigens and presentations by DCs. This was in line with our findings that naked antigen (J8, or PADRE-J8) without a nanoparticulate delivery system could not upregulate CD40, MHC-II, CD80 or CD86 expression on DC2.4 cells.…”
Section: Discussionsupporting
confidence: 57%
“…In our previous attempts to develop efficient vaccine delivery systems, we have demonstrated that conjugation of the polyleucine moiety to a peptide antigen greatly enhanced antigen-specific humoral immune responses [ 20 , 21 , 23 , 24 , 25 , 26 , 27 ]. We also found that the polymer–antigen conjugate D-8Qm once formulated into liposomes ( L1 ) was able to eradicate, to some extent, seven-days-old cancer in mice [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observed nitrogen–carbon ratio for D-8Qm (N/C = 0.115) was higher than that of the polymer alone (N/C= 0.017) and corresponded to 83% of the substitution rate of the dendrimer with 8Qm peptide (similar to that previously reported at 85% [ 19 ]). Both D-8Qm and pLeu-8Qm , as amphiphilic conjugates, were easily incorporated (anchored) into liposomes [ 19 , 21 ] to form L1 and L2 , respectively ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation